1997
DOI: 10.1037/0021-843x.106.1.104
|View full text |Cite
|
Sign up to set email alerts
|

A day at a time: Predicting smoking lapse from daily urge.

Abstract: Smokers who recently quit (N = 214) monitored smoking urges for up to 26 days after quitting. Computers administered 4-5 assessments daily at random times; participants rated urges on waking and when they experienced temptation episodes. Urge intensity after cessation did not generally exceed urges reported during baseline ad lib smoking. Urge intensity and temptation frequency consistently declined over the quit period. Controlling for urge intensity at baseline, all daily urge intensity measures predicted la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
388
5
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(419 citation statements)
references
References 50 publications
(103 reference statements)
22
388
5
4
Order By: Relevance
“…Participants who reported high levels of withdrawal, tension, or craving for the relief of negative affect after 12 h of abstinence were more likely to initiate smoking earlier during the delay period, which may suggest that the primary motivation for initiating smoking was alleviation of the negative symptoms related to acute abstinence. This notion is supported by the findings of several smoking cessation studies which demonstrated that a rapid increase in withdrawal symptoms, negative affect, and craving and the subsequent desire to relieve this aversive symptomatology is the most reliable predictor of a smoking lapse (Shiffman et al, 1996a;Shiffman et al, 1997b;Shiffman et al, 2002;Shiffman and Waters 2004).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Participants who reported high levels of withdrawal, tension, or craving for the relief of negative affect after 12 h of abstinence were more likely to initiate smoking earlier during the delay period, which may suggest that the primary motivation for initiating smoking was alleviation of the negative symptoms related to acute abstinence. This notion is supported by the findings of several smoking cessation studies which demonstrated that a rapid increase in withdrawal symptoms, negative affect, and craving and the subsequent desire to relieve this aversive symptomatology is the most reliable predictor of a smoking lapse (Shiffman et al, 1996a;Shiffman et al, 1997b;Shiffman et al, 2002;Shiffman and Waters 2004).…”
Section: Discussionmentioning
confidence: 71%
“…A series of reports by Shiffman and colleagues have identified contextual changes in mood and motivation, proximal to the lapse event itself, that promote a lapse into smoking, such as increases in negative affect, nicotine withdrawal, and urge to smoke (Shiffman et al, 1996a;Shiffman et al, 1997b;Shiffman et al, 2002;Shiffman and Waters 2004). Additionally, individuals who possess certain traits, including high anxiety, low distress tolerance, and a high severity of nicotine dependence, are also more at risk to lapse in early abstinence (Shiffman et al, 1996b;Shiffman et al, 1997a;Brown et al, 2005;Zvolensky et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from animal studies suggests that nicotine withdrawal results in significant decreases in brain reward function, which is a potential explanation for the physiological basis of smoking relapse (Epping-Jordan et al 1998). In studies with humans, withdrawal symptoms have been identified as a predictor of relapse from smoking cessation (Swan et al 1996;Shiffman et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To balance baseline variables between the two conditions, treatment assignment used an automated algorithm stratifying on these factors empirically known to predict smoking cessation: gender (male/female), quit attempts in past 12 months (yes/no), binge alcohol use in past 30 days (yes/no), and positive screen for depression in past 3 months (yes/no; Hughes & Kalman, 2006;Perkins et al, 2008;Shiffman et al, 1997;Zhu, Sun, Billings, Choi, & Malarcher, 1999). Randomized study arm assignments were computer generated and concealed from participants after eligibility was determined and consent for participation was obtained.…”
Section: Randomizationmentioning
confidence: 99%